Do Princípio da Dignidade da Pessoa Humana e o Conhecimento Tradicional Associado ao Manejo Pesqueiro: um estudo de caso na Comunidade Santo Antônio do rio Urubu, no município de Boa Vista do Ramos – Amazonas - Aguiar, Denison Melo de (2011)
The main objective of this dissertation is the theoretical study of the principle of human dignity and the protection of the traditional knowledge associated with the fisheries management in its interface. In the factual level the fishing agreements at Comunidade Santo Antônio do Rio Urubu in Boa Vista do Ramos in the State of Amazonas, Brazil are examined. The study is justified as follows: a) in the social side - there is a real need for indigenous peoples and traditional communities to participate in the management of the fisheries resources, based in their traditional knowledge and b) on the legal side - the fishing agreements are formal rules, originated from the community uses and customs about the fishing resources, constituting a kind of traditional knowledge protection. The general objective is to analyze the relationship between the principle of human dignity and the traditional knowledge associated to the fisheries management, via a case study of the Fisheries Agreement No. 11, from March 20, 2003 in the community above. In summary, one can conclude that in the foreground, that is necessary to elaborate a principle which corresponds to a collective reality, incorporating the principle of human and community dignity, as well as in designing a principle of human dignity that can be manipulated as information in decision- making and the fisheries agreement, in order that they have effectiveness, efficiency, efficacy on the principle of human and community dignity in the the fisheries agreement. So the interface between them is evident in the ecological dimension of the principle of human dignity, especially when it comes to the fishing agreements as a means of socioenvironmental conflict resolution and traditional knowledge protection related to the fisheries management. Concerned to to above community in factual terms, the relation between principle of human dignity and the traditional knowledge relating fisheries management in this fishing agreement is the formation of a etnoictiological law. Community participation ranged from preparation to implementation, albeit it is necessary their greater participation in terms of the assessment and monitoring of fishing agreements. It is suggested that to have better fiscalization is necessary to training voluntary environmental agents in the community and with stakeholders, in monitoring, articulate alliances with research groups from universities and institutes in the fishing sector. Concerning to the assessment, it must have a better mutual stakeholders monitoring in the preparation of fishing agreements. Therefore, it necessary a better political articulation of the community and the stakeholders in the fishing agreements, as the political articulation is existential, as when they receive dental care and medical assistance and dental group Americans and with the City of Boa Vista Ramos. From all this, the fishing agreements can be an instrument of political communities to be effective, even in part, the principle of human and community dignity through traditional knowledge associated with the fisheries management.